Proteins of allogeneic hepatocytes and pharmacological preparations for the correction of immunometabolic disorders in experimental liver pathology - Ekaterina S. Litvinova; Nikolay N. Konoplya; Anastasiya A. Shulginova; Anastasiya V. Kharchenko (Belgorod National Research University, 2021)
Introduction: The relationship of numerous metabolic shifts, disorders of hepatocytes functional activity resulting from hypoxia and toxic liver damage with the function of the immune system has not been sufficiently studied so far, nor have the most effective methods of pharmacological correction been established. Materials and Methods: The studies were carried out on 603 mature male Wistar rats and 45 mice. Acute toxic liver damage (ATLD) was modeled by intramuscular introduction of carbon tetrachloride; acute liver ischemia (ALI) was caused by clamping the hepatoduodenal ligament for 20 minutes; chronic alcohol intoxication (CAI) was modeled by forced intragastric administration of 20% ethanol solution for 60 days. Isolation of xenogeneic (murine) and allogeneic (rat) hepatocytes from newborn mice and rats was carried out according to the method of Berry and Friend (1969); culture fluid of hepatocytes and its protein fractions were prepared according to our developed techniques. The obtained biological material was intraperitoneally introduced into the rats with ATLD, ALI, and CAI. Results and Discussion: In all the models of the liver damage, there developed morphological and biochemical signs of the liver damage, impaired congenital and adaptive immunity, oxidative stress, increased lipid peroxidation processes. Conclusion: The introduction of allogeneic hepatocytes, culture fluid obtained on their basis,and proteins isolated from it with MW less than 130 kDa to the recipients with toxic and ischemic liver damage more effectively corrects the pathologic changes in the liver in comparison with xenogeneic hepatocytes, their culture fluid and pharmacological preparations (combinations of Essentiale N and Hypoxenum or Heptral and Mexicor).